Improve Casting Properties of Steel Alloy - N. M. , Saidmakhamadov; K. Kh., Abdullaev; N. Kh. , Tadjiev; L. T., Chorshanbieva; U. Ya., Haydarov (Miasto Przyszłości, 2023)
In this article, in order to improve the casting properties of steel alloys, the method of liquefaction of high-quality structural steel alloy in an electric arc furnace was developed. In addition, in the process of liquefaction of high – quality steel alloy, the improvement of the mechanical properties of high – quality steel alloy was achieved by adding various fluxes and modifiers to the composition of the alloy.